ALWAYS-ALREADY: LIBRARY SERVICES IN SUPPORT OFTHE DIGITAL HUMANITIES - Worthey, Glen (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2016)
The thesis of this paper is simple: the digital humanities (DH) can and should make a happy home in the modern research library, and this has been true for decades. What? – Some may ask. – You mean to say that DH has been around for decades? Yes, – I say – and not only that, but DH has some very serious theoretical and practical forebears from almost a hundred years ago: the Russian Formalists, who even today have some important things to teach us not only about DH in general, but also about DH in the library.